Malawi COVID-19 Urban Cash Intervention Process Evaluation Report - Paul, Boban Varghese; Msowoya, Chipo; Archibald, Edward; Sichinga, Massimo; Campero Peredo, Alejandra; Malik, Muhammad Abdullah Ali (World Bank, Washington, DC, 2022)
This report presents the findings of a process evaluation for the Coronavirus disease 2019 (COVID-19) urban cash intervention (CUCI) program. The CUCI was initiated by the Government of Malawi in 2020 to help mitigate the adverse health and economic effects of COVID-19 on urban poor populations in Lilongwe, Blantyre, Zomba, and Mzuzu. CUCI is the first major cash transfer program in Malawi to focus on urban areas. It therefore provides a conducive and fertile learning ground for shaping future policy and programming, both in terms of urban cash transfers and shock-responsive interventions. The goal of this process evaluation is to understand the quality of implementation of CUCI at each stage of the delivery chain, with a view to informing future policies and programs. The study looks at what, how, and why CUCI activities were implemented, what worked well, and what did not work well along the nine stages of CUCI’s delivery chain. The assessment also integrates the four building blocks of adaptive social protection, i.e., programs; data and information systems; finance; and institutional arrangements and partnerships - across all stages of the delivery chain. The process evaluation plans to draw lessons that can inform medium- to long-term considerations regarding the design and implementation of both urban safety nets and shock sensitive social protection policies and programs. The section lays out the context in which the CUCI was designed and implemented. It does this through examining the impacts of COVID-19 and social protection responses by governments - firstly at a global and regional level, and then with regard to Malawi.